Modeling the interaction between powder particles and laser heat sources - Baloyi, P.; Desai, D. A.; Arthur, N. K. K.; Pityana, S. L. (Frontiers in Manufacturing Technology, 2024)
This study investigates the spheroidization of titanium Ti-6Al-4V powder particles using numerical models developed in Abaqus and OpenFOAM. Spherical particles are crucial in powder-based additive manufacturing due to their superior flowability, packing density, and mechanical properties, enhancing printing precision and the quality of final products. While conventional techniques such as gas atomization and plasma spheroidization have been extensively researched, the potential of laser spheroidization remains underexplored. To address this gap, detailed numerical analyses of laser spheroidization were conducted, modeling heat transfer from the laser to powder particles using a transient uncoupled heat transfer method with latent heat considerations, while particle deformation was simulated with a phase-fraction-based interface-capturing approach integrated with Navier-Stokes equations. The results, validated against analytical models, indicate that particles within the 20–80 μm range experience optimal spheroidization within a 0.005-second residence time under laser heating, with particles smaller than 30 μm reaching evaporation temperatures of 5,000°C, while larger particles reshape without evaporating under a typical heat flux of 94 MW/m2 (1.8 kW laser power). This study demonstrates that laser spheroidization of Ti-6Al-4V powder can potentially increase powder yield by 10%, offering higher power density and shorter melting times compared to plasma spheroidization, thus presenting a more efficient alternative for achieving spherical particles of specific sizes.